Modeling and vibration control of piezoelectric actuator - Muhammad, Bashir Bala (2015)
The piezoelectric actuator is a voltage spring system that behaves in similar characteristic to mechanical mass spring system. It converts electrical signal to physical displacement. The displacements profile of the piezoelectric actuator shifts due to hysteresis and creep during actuation. Static models of piezoelectric actuator were developed with different equations in the past. However, static (non-dynamic) piezoelectric actuator models were not represented by single transfer function. Furthermore, the modelling of dynamic (vibrating) piezoelectric actuator was not considered. In this work, we presented the behaviour of the piezoelectric actuator in terms of mechanical displacement from applied electric potential. The transfer function mathematical model was generated representing the actuator characteristics. The vibration model that can vibrate at desired frequency of the actuator was also developed. The models were developed by system identification from experimental results. A high resolution microscope together with the image processing technique was used to obtain the system characteristics. Simulation using Matlab simulink was used to validate the experiment (The hysteresis was reduced by 90 % and the vibration was reduced to 97 %.). These models can be used to develop the controller for controlling vibration profile. It can also be used for desired micro actuation. It can also be used for desired micro actuation.